Cationic poly(amide-imide)-conjugated camptothecin prodrug with variable nanomorphology for efficient reductive-responsive drug delivery. (15th January 2020) - Wang, Mengzhen; Yan, Junjie; Li, Cong; Wang, Xinyu; Xiong, Jianjun; Pan, Donghui; Wang, Lizhen; Xu, Yuping; Li, Xiaotian; Yang, Min
Graphical abstract: Highlights: Amphiphilic poly(amide-imide)-based camptothecin prodrugs were synthesized. PAI-based polymer prodrugs self-assembled into variable nanomorphologies in aqueous solution. Cationic PAI-based prodrug nanoparticles presented a rapid cellular internalization (<2 h). PAI-based prodrug nanocarriers showed potential in combination chemotherapy. Abstract: Poly(amide-imide)s (PAIs) present limited use in bioapplications due to their poor aqueous solubility and difficulty in functional accessibility. Herein, we prepared PAI-based prodrugs by leveraging aliphatic PAIs as the polymer scaffolds and conjugating camptothecin (CPT) via thiol-disulfide exchange reaction. The degree of CPT attachment can be smoothly controlled by initial feed ratios of PEG and a pyridinedisulfide-modified CPT precursor. Due to the abundant secondary amine groups in PAI backbones, amphiphilic PAI-CPT prodrugs self-assembled into cationic nanoparticles and showed an efficient cellular internalization (<2 h). The presence of disulfide linkers between PAI scaffolds and CPT endowed PAI-CPT prodrugs a reductive-responsive drug release profile. Moreover, when PAI-CPT prodrug nanoparticles were further used as nanocarriers, doxorubicin (DOX) was additionally encapsulated and variable nanomorphologies (nanospheres, branched nanoparticles) were obtained, and an enhanced chemotherapy efficacy was achieved as well.